Community consultation for Exception from Informed consent (EFIC) before and during the COVID-19 pandemic - David J. Gagnon; Richard R. Riker; Frank Chessa; Christine Lord; Ashley Eldridge; Meghan Searight; Sarah Bockian; Barbara McCrum; Teresa L. May; Douglas Sawyer; David B. Seder (Resuscitation Plus, 2022)
Aim: Describe community consultation and surrogate consent rates for two Exception From Informed Consent (EFIC) trials for out-of-hospital cardiac arrest (OOHCA) - before and during the COVID-19 pandemic. Methods: The PEARL study (2016–2018) randomized OOHCA patients without ST-elevation to early cardiac catheterization or not. Community consultation included flyers, radio announcements, newspaper advertisements, mailings, and in-person surveys at basketball games and ED waiting rooms. The PROTECT trial (2021-present) randomizes OOHCA survivors to prophylactic ceftriaxone or placebo; the community consultation plan during the pandemic included city council presentations, social media posts, outpatient flyers, but no in-person encounters. Demographics for PROTECT community consultation were compared to PEARL and INTCAR registry data, with p-value < 0.05 considered significant. Results: PEARL surveyed 1,362 adults, including 64 % ≥60 years old, 96 % high school graduates or beyond; research acceptance rate was 92 % for the community and 76 % for personal level. PROTECT initially obtained 221 surveys from electronic media – including fewer males (28 % vs 72 %,p < 0.001) and those > 60 years old (14 % vs 53 %;p < 0.001) compared to INTCAR. These differences prompted a revised community consultation plan, targeting 79 adult in-patients with cardiac disease which better matched PEARL and INTCAR data: the majority were ≥ 60 years old (66 %) and male (54 %). Both PEARL and PROTECT enrolled more patients using surrogate consent vs EFIC (57 %, 61 %), including 71 % as remote electronic consents during PROTECT. Conclusions: Community consultation for EFIC studies changed with the COVID-19 pandemic, resulting in different demographic patterns. We describe effective adaptations to community consultation and surrogate consent during the pandemic.